Hip replacements at the Hospital Nacional Guillermo Almenara, 1995-1997 - Bermúdez García, Alejandro (1998)
OBJECTIVES: To review the main features of hip replacements, both partial and total, performed at the Hospital Nacional Guillermo Almenara, Lima-Peru, between 1995-1997. METHODS: a descriptive, cross-sectional, observational and partially prospective review of 232 clinical records from 325 surgical hip replacements. RESULTS: Patients with ages between 59 and 70 years old (60% females), most of them were homeworkers and come from Lima. Coxofemoral artrosis was the commonest etiology conducing to a total arthroplasty, and femoral head fracture the cause of partial arthroplasty. The most frequent short term complication was surgical wound infection, being S. epidermidis the main pathogenic microorganism isolated, and the most frequent long-term complication was dislocation of the implant. Mortality, as direct cause, was uncommon, and it is associated to patient self-characteristics. Total replacement was most frequent (81%) than partial, with a mean length of stay of 29 d; with post-operative periods of 5 d for partial replacements and 18 d for total replacements.